Language, Migration and Multilingualism in the Age of Digital Humanities - Issel-Dombert, Sandra; Soria, Ignacio Andrés; Morgenthaler García, Laura (De Gruyter, 2023)
The digital turn has far-reaching implications for linguistic research, from data collection and analysis to storage infrastructure. It also brings about profound changes in epistemological and ethical practices as well as in data protection. This volume gathers 11 case studies that explore the impact of digitization in the fields of multilingualism, migration and language in Spanish-speaking contexts.